Use of rituximab in mature, high-grade and advanced-stage pediatric B-lineage non-Hodgkin lymphomas: a systematic review, meta-analysis and the Brazilian reality - Castro, Alejandra Adriana Cardoso de; Oliveira, Liana Alves de; Andrade, Diancarlos Pereira de; Carbone, Edna Kakitani; Rosati, Roberto (Frontiers in Pediatrics, 2025)
ObjectivesRituximab is a valuable agent for treating adult B-cell non-Hodgkin lymphoma (B-NHL), and several studies have tested its efficacy in children with mature, high-grade B-NHL. The aim of the present study was to systematically review the use of rituximab in children and adolescents with high-grade mature B-NHL and to conduct a meta-analysis of the evidence. Since access to this medication in public health systems in low- and middle-income countries is complex, we were also interested in mapping access to it in Brazil.MethodsWe conducted a systematic review and meta-analysis on the survival of pediatric patients with mature, high-grade and advanced-stage B-NHL treated with rituximab in combination with chemotherapy in first-line treatment or later. Patients' access to the medication was evaluated through a questionnaire sent to oncologists in Brazilian pediatric oncology centers.ResultsWe selected 17 trials, which were subsequently grouped by disease type and line of therapy. In patients receiving first-line treatment, excluding those with primary mediastinal B-cell lymphoma (PMBL), the use of rituximab resulted in (1) better event-free survival [Hazard Ratio of 0.37 (0.22, 0.61); p < 0.01]; (2) a reduced risk of events [odds ratio of 0.44 (0.26–0.76); p = 0.003]; and (3) a reduced risk of death [odds ratio of 0.44 (0.21–0.89); p = 0.02]. In refractory or relapsed (R/R) patients, rituximab use was associated with a decreased chance of death [odds ratio of 0.25 (0.09–0.75); p = 0.01]. Additionally, our survey included 31 Brazilian centers, 63% of which reported bearing the cost of rituximab.ConclusionRituximab improves outcomes in pediatric patients receiving first-line treatment for high-grade B-NHL (except PBML) and overall survival in R/R patients. However, access to rituximab in Brazilian hospitals is currently dependent on centers supporting its economic burden.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO (CRD42021292912).